A Fatal Case of Primary Basaloid Squamous Cell Carcinoma in the Intrahepatic Bile Ducts. (7th October 2014) - Kirkegaard, Johan; Grunnet, Mie; Hasselby, Jane Preuss
Abstract : Primary squamous cholangiocellular carcinomas are very rare. We describe a case of a 67-year-old man, who underwent chemotherapy and surgery for a right-sided liver tumor with an unusual presentation of metastasis to a lymph node in the left armpit. The patient was asymptomatic at the time of diagnosis but expired 20 months after surgery with epidural, lung, and spine metastasis. In addition to the unusual clinical presentation, the diagnosis of the liver tumor was that of a primary basaloid squamous cell carcinoma of the intrahepatic bile ducts, an entity with only one previous report in the literature.